Intentions to use bike-sharing for holiday cycling: An application of the Theory of Planned Behavior - Kaplan, Sigal; Manca, Francesco; Nielsen, Thomas A. S.; Prato, Carlo G. (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
This study explored the behavioral factors underlying tourist intentions to use urban bike-sharing for recreational cycling while on holiday. The analytical framework relied on the Theory of Planned Behavior relating tourist intentions to pro-cycling attitudes, interest in bicycle technology, pro-cycling subjective norms and perceived cycling ease. The case-study focused on the new bike-sharing system in Copenhagen (Denmark) and questioned 655 potential tourists about a hypothetical holiday scenario. Structural equation models revealed: (i) the great interest in using bike-sharing, frequently and for multiple purposes; (ii) the relation between holiday cycling and living in a cycling-friendly country, past cycling experience and habitual mode choice; (iii) the appeal of electric bicycles to tourists with high interest in bicycle technology, low perceived cycling ease and weak pro-cycling norms; (iv) the relation between frequent and multi-purpose cycling intentions and stronger pro-cycling attitudes and norms, and greater perceived likelihood that the holiday partners would cycle.